THE SYMPTOM AND MEDICATION MONITORING WITH LUPIE DIARY IN PEDIATRIC SYSTEMIC LUPUS ERYTHEMATOSUS - Arie Kusumaningrum; Nadia Zahra Amelia (Spectra Clinical Case Reports Journal, 2026)
Pediatric systemic lupus erythematosus (pSLE) in low-and-middle-income countries often leads to rapid organ damage due to complex treatment regimens and limited specialized care. Effective home-based symptom monitoring is critical to detect early flares, yet conventional tracking is often suboptimal, necessitating tailored digital health solutions like the "Lupie Diary" application to capture real-time clinical fluctuations. This case report describes the nurse-facilitated implementation of "Lupie Diary" to enhance self-management in three adolescent female patients in a resource-limited Indonesian hospital. Based on Indonesian nursing standards, primary diagnoses included Hyperthermia, Nutritional Deficit, Impaired Skin Integrity, Nausea, and Readiness for Enhanced Health Management. The intervention spanned 4 weeks, comprising a 3-day hospital-based training phase on daily symptom logging and medication reminders, followed by weekly remote nursing tele-monitoring at home. As a direct result of utilizing the application, the patients demonstrated significant improvements in treatment adherence, systematic symptom tracking, and active engagement, heavily facilitated by the nurse's role as a clinical educator and technology facilitator. This approach highlights the critical role of nurses in bridging hospital-to-home care through technology-integrated, family-centered interventions. Embedding simple digital tools into standard nursing care plans is a viable, effective strategy to empower pediatric patients with complex chronic diseases despite resource constraints.